Ventilation blocks: Design feature in Malaysia public schools - Nordin, Norhaslin; Ismail, Muhammad Azzam; Mohd Ariffin, Ati Rosemary (Faculty of Built Environment, University of Malaya, 2019)
Hot and humid climate conditions have always been a challenge to building designers in tropical countries. Mouldy façade can emerge within a few days due to heavy rain and a room can easily become hot and musty. These are among the major issues caused by improper ventilation. To overcome these problems, ventilation block, an ingenious building element that has a long history, is widely used in tropical countries. It provides comfort through cross ventilation, permitting daylight and offering protection from heavy rainfall and, giving aesthetic value. This paper is part of the main research on the findings of passive design elements in Malaysia schools buildings. The main purpose of this paper is to investigate, identify and discuss on the types, the design features and the characteristics of the ventilation blocks found on the existing primary school buildings in Kuala Lumpur territory, Malaysia. A total of 85 from a list of 201 schools were visited and observation was made. The schools were selected and categorised according to the years they were founded and based on the findings of their architectural design influences. It was found that there were at least 10 different ventilation block designs among the schools sampled in the present study which were built between the 1950s and 1960s. This element can be found in various locations of the buildings. Nevertheless, the purpose of such element was clearly to provide good ventilation and comfort to the occupants. Combining architecture and cross ventilation as a design feature has led to the implication of using ventilation block may not only solve the problems identified but also add value to the building and a present a convincing strategy towards sustainable design approach. © 2019, University of Malaya. All rights reserved.